The Effect of Using Google Forms to Improve English Listening Skills - Alip Purnomo; Qausya Faviandhani; Agung Ariwibowo; Budi Purwoko; Nunuk Hariyati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aimed to determine the effect of using Google Form to improve students' English listening skills. This study uses an experimental research type conducted in one class. The sample in this study was class A students of the Management study program at Narotama University, totaling 25 students. The results of the study showed a t sig value of 0.000 <0.05, which means that there is a difference in the average pretest and posttest scores of students, which means that there is an influence of using Google Forms to improve students' English listening skills. The results of this study were that students felt more involved and motivated when using Google Form compared to conventional listening methods, the use of Google Form in listening training allowed students to get direct feedback, Google Form increased student motivation in learning listening and Google Form allowed lecturers to collect data and analyze the level of student understanding more easily and accurately